A case Report and Literature Review of Spindle Cell Squamous Cell Carcinoma of the Larynx - Zghal, Mouna; Makni, Saadia; Mellouli, Manel; Bouhamed, Marwa; Chaari, Chiraz; Boudawara, Tahya Sallemi; Ayedi, Lobna (Issues and Developments in Medicine and Medical Research Vol. 4, 2022)
Spindle cell squamous carcinoma (SCSCC) is a rare malignant tumor, with two contingents squamous cell carcinoma and sarcomatoid proliferation. It remains uncommon in the larynx and represents only 1% of SCSCC of the head and neck. This tumor still poses diagnostic and therapeutic challenges. The aim of this work is to current knowledge epidemiological, clinico-pathological, treatment and prognostic features of this rare entity, by reporting three cases of laryngeal SCSCC diagnosed in our department, we also performed a literature review. The patients were smoker men aged 50, 66 and 66 years old respectively. Dysphonia was the mean symptom. The tumor involves the vocal cord in all cases. The patient underwent laryngectomy with bilateral neck dissection. Histological examination confirmed the diagnostic of SCSCC in all cases. One tumor showed basaloid squamous cell carcinoma with sarcomatous transformation and osteosarcoma. Immunohistochemical analysis performed in one patient was positive for vimentine, SMA, PS100, focally for EMA and negative for keratin and P63. One case presented lymph nodes metastases and an adjuvant radiotherapie was preconised for this patient. All patients were well controlled after treatment and there was no recurrence during the following up.